2018
DOI: 10.5664/jcsm.7534
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adverse Pregnancy Outcomes With Self-Reported Measures of Sleep Duration and Timing in Women Who Are Nulliparous

Abstract: Study Objectives: To examine the relationship of self-reported sleep during pregnancy with adverse pregnancy outcomes. A secondary objective was to describe the concordance between self-reported and objectively assessed sleep during pregnancy. Methods: In this prospective cohort, women completed a survey of sleep patterns at 6 to 13 weeks' gestation (visit 1) and again at 22 to 29 weeks' gestation (visit 3). Additionally, at 16 to 21 weeks (visit 2), a subgroup completed a week-long sleep diary coincident with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
1
34
2
2
Order By: Relevance
“…The use of sensors and actigraphy to monitor sleep quality, activity patterns, and movement in patients is a novel approach to the quantification of lifestyle-related behaviors that might affect health [135,136]. Although this strategy has been underexplored, altered sleep patterns during pregnancy have been shown to lead to differential gene expression in mothers [137].…”
Section: Challenges and Potential Of Complex Datamentioning
confidence: 99%
“…The use of sensors and actigraphy to monitor sleep quality, activity patterns, and movement in patients is a novel approach to the quantification of lifestyle-related behaviors that might affect health [135,136]. Although this strategy has been underexplored, altered sleep patterns during pregnancy have been shown to lead to differential gene expression in mothers [137].…”
Section: Challenges and Potential Of Complex Datamentioning
confidence: 99%
“…We assessed sleep complaints by means of questions to the pregnant women. Such subjective measures of sleep duration and sleep efficiency have previously been shown to be correlated with objective measures [10,21], but may obviously be affected by the individual's reporting style. The degree of trouble and the level of worries can, however, only be assessed by the women themselves.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The mechanisms behind are unclear, but sleep disturbances may produce changes in the hypothalamic-pituitaryadrenal axis and abnormal immune/inflammatory reactions [7]. Further, sleep is critical for glucose metabolism and several meta-analyses found that both self-reported and objectively measured sleep is assoiated with hyperglycemia and an increased risk of gestational diabetes mellitus (GDM) [8][9][10]. Sleep is also important for blood pressure; both short and long sleep duration as well as poor sleep quality are associated with elevated blood pressure [11], measured with Pittsburgh Sleep Quality Index (PSQI) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Gebelikte görülen uyku sorunları gebelikte aşırı kilo alımı, yaşam kalitesinin düşmesi, doğum sonrası ruh halinin kötüleşmesi, gestasyonel diyabetes mellitus ve yüksek arteryal kan basıncı gibi riskli durumların ortaya çıkmasını tetikleyebilmektedir (6,25,32,37,38). Gebelikte yaşanan uyku sorunlarının fetüs sağlığına da düşük doğum ağırlığı ve düşük apgar skoru gibi olumsuz etkileri bulunmaktadır (29,39).…”
Section: Gebelikte Uyku Sorunlarının Perinatal Süreçteki Etkileri Anne Ve Fetüs/yenidoğan Sağlığına Etkisiunclassified
“…Bir çalışmada, gebelerin gece saat 05'ten sonra uyumasının gestasyonel diyabetes mellitus riski ile ilişkili olduğu bulunmuştur. Bunun sebebinin biyolojik nedenli olabileceği, uyku zamanlamasının bozulmasının geceleri yapay ışığa maruz kalınarak melatonin salgılanmasını baskılayabileceği ve kronik bozulmaya yol açabileceği belirtilmiştir (37). Kuzey Tayvan'da gebe kadınlarla yapılan bir çalışmada; horlamanın, yüksek diyastolik kan basıncının ve yüksek ortalama arteriyel kan basıncının anlamlı bir belirleyicisi olduğu bulunmuştur.…”
Section: Gebelikte Uyku Sorunlarının Perinatal Süreçteki Etkileri Anne Ve Fetüs/yenidoğan Sağlığına Etkisiunclassified